A fully integrated microdevice for biobarcode assay based biological agent detection1. Issue 13 (7th July 2015) - Cho, Minkyung; Chung, Soyi; Kim, Yong Tae; Jung, Jae Hwan; Kim, Do Hyun; Seo, Tae Seok
<x xml:space="preserve">Abstract</x> We reported a fully integrated microdevice that is capable of performing a biobarcode assay to detect multiplex biological agents with high speed, accuracy and sensitivity.